FRI0348 Feasibility and Validity of Patient Reported Outcome Measurement Information System (PROMIS) in Systemic Lupus Erythematosus. (15th July 2016) - Kasturi, S.; Burket, J.C.; Berman, J.; Kirou, K.; Levine, A.B.; Sammaritano, L.R.; Mandl, L.A.
Abstract : Background: Accurate measurement of patient reported outcomes (PROs) is important in systemic lupus erythematosus (SLE), a heterogeneous disease in which similar symptoms can have disparate impact across patients. PROMIS offers dynamic computer adaptive tests (CATs) to precisely and efficiently measure PROs in a variety of relevant domains. Objectives: The aims of this study were to: 1) assess the feasibility of administering PROMIS CATS serially to SLE outpatients 2) correlate PROMIS CATs with legacy PRO measures, SLE disease activity and organ damage 3) assess retest reliability of PROMIS CATs. Methods: Adults meeting American College of Rheumatology SLE classification criteria were recruited from a SLE Center of Excellence. Subjects completed the Short Form-36 (SF-36), LupusQoL-US, and selected PROMIS CATs. SLE disease activity, flare, and damage were evaluated with the SELENA-SLEDAI and SLICC-ACR damage index. PROMIS domains were compared with disease activity, damage, and similar domains in legacy instruments using Spearman correlations. Retest reliability was evaluated among subjects reporting stable SLE activity at two assessments one week apart using intraclass correlation coefficients (ICC). Results: Of 198 patients approached, 163 (82%) completed at least one assessment, 130 (80%) completing it remotely. 138 (85%) completed a retest. Most PROMIS domains showed moderate to strong correlations with similar domains in both legacy instruments (Figure 1 ). However, correlations between PROMIS and the physician global assessment, SELENA-SLEDAI, and SLICC-ACR damage index were generally weak and statistically insignificant. PROMIS CAT retest ICCs ranged from 0.74 to 0.89. Conclusions: To our knowledge, these data are the first to show that PROMIS CATs can be successfully administered to a diverse cohort of SLE patients at the point of care or remotely, and are valid and reliable for many SLE relevant domains. Importantly, PROMIS scores did not correlate well with physician-derived measures. This disconnect between objective signs and symptoms and the subjective patient disease experience underscores the crucial need to integrate PROs into clinical care to ensure optimal disease management. Acknowledgement: Funding for this study was provided by the Rheumatology Research Foundation Scientist Development Award. Disclosure of Interest: None declared